2022
DOI: 10.1097/md.0000000000028843
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of acupoint herbal patching for constipation after stroke

Abstract: Background:Constipation is one of the common problems in stroke patients, which seriously affects the life quality of patients and even leads to the recurrence of cerebrovascular disease. The clinical trials of acupoint herbal patching (AHP) in the adjuvant treatment of constipation after stroke (CAS) is currently in progress. However, there is no systematic review or meta-analysis to evaluate the effects of AHP on CAS.Methods:We will search articles in 8 electronic databases including the Cochrane Central Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies have revealed that acupuncture has a bidirectional adjustment to the heart rate of healthy people, which is equivalent to the impact of acupuncture on balancing yin and yang, [21] and the vagus nerve is the key reaction. [22,23] Modern studies [23][24][25][26] have found that Neiguan is close to the median nerve and overlaps with the innervated nerve segments of the heart, and the information of acupuncture at Neiguan can reach the cardiovascular center, namely the nucleus of the solitary tract, the posterior hypothalamus and the preoptic area-the front part of the hypothalamus. In the early stage of our research group, a patient with mild autonomic dysfunction in the convalescence period of stroke and a severe patient were acupunctured with bilateral Zusanli and bilateral Neiguan, respectively, and we found that the HRV values of the 2 patients reached equilibrium at 20 minutes and 25 minutes of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that acupuncture has a bidirectional adjustment to the heart rate of healthy people, which is equivalent to the impact of acupuncture on balancing yin and yang, [21] and the vagus nerve is the key reaction. [22,23] Modern studies [23][24][25][26] have found that Neiguan is close to the median nerve and overlaps with the innervated nerve segments of the heart, and the information of acupuncture at Neiguan can reach the cardiovascular center, namely the nucleus of the solitary tract, the posterior hypothalamus and the preoptic area-the front part of the hypothalamus. In the early stage of our research group, a patient with mild autonomic dysfunction in the convalescence period of stroke and a severe patient were acupunctured with bilateral Zusanli and bilateral Neiguan, respectively, and we found that the HRV values of the 2 patients reached equilibrium at 20 minutes and 25 minutes of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of evidence regarding patient outcomes will be assessed by the Grading of Recommendations Assessment, Development, and Evaluation methodology (GREAD). [13] The results of the quality of evidence assessment will be categorized into 4 grades: high, medium, low, and very low.…”
Section: Methodsmentioning
confidence: 99%